2006
DOI: 10.1158/0008-5472.can-05-4400
|View full text |Cite
|
Sign up to set email alerts
|

Role of Focal Adhesion Kinase and Phosphatidylinositol 3′-Kinase in Integrin Fibronectin Receptor-Mediated, Matrix Metalloproteinase-1–Dependent Invasion by Metastatic Prostate Cancer Cells

Abstract: A 5 B 1 Integrin interacts with the PHSRN sequence of plasma fibronectin, causing constitutive invasion by human prostate cancer cells. Inhibition of this process reduces tumorigenesis and prevents metastasis and recurrence. In this study, naturally serum-free basement membranes were used as in vitro invasion substrates. Immunoassays were employed to dissect the roles of focal adhesion kinase (FAK), phosphatidylinositol 3 ¶-kinase (PI3K), and protein kinase CD (PKCD) in A 5 B 1 -mediated, matrix metalloprotein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
89
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 53 publications
5
89
0
Order By: Relevance
“…Our current findings indicate that the ECM glycoprotein, fibronectin, specifically promotes A549 lung cancer cell migration and invasion. Consistent with previous reports that FAK has a critical role in promoting cell migration and invasion (Mukhopadhyay et al, 2005;Zeng et al, 2006), we found an increased activation of FAK in A549 cells grown in fibronectin-coated plates. Focal adhesion kinase activation was determined by increased phosphorylation of FAK at its Tyr397, Tyr861, and Tyr925 residues.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our current findings indicate that the ECM glycoprotein, fibronectin, specifically promotes A549 lung cancer cell migration and invasion. Consistent with previous reports that FAK has a critical role in promoting cell migration and invasion (Mukhopadhyay et al, 2005;Zeng et al, 2006), we found an increased activation of FAK in A549 cells grown in fibronectin-coated plates. Focal adhesion kinase activation was determined by increased phosphorylation of FAK at its Tyr397, Tyr861, and Tyr925 residues.…”
Section: Discussionsupporting
confidence: 93%
“…There have been suggestions that activation of PI3K regulates the migration and invasion of various cancer cells (Reiske et al, 1999;Zeng et al, 2006). Despite these findings, the specific role of PI3K in controlling lung cancer cell migration and invasion, particularly in relation to FAK signalling, has been elusive.…”
Section: Discussionmentioning
confidence: 99%
“…This FAK signalling pathway also seems to operate in noncancerous cells (Segarra et al, 2005). There have been reports linking other extracellular proteases, such as MMP-9 (Mon et al, 2006a), MMP-1 (Zeng et al, 2006) and uPA with FAK signalling in other tumour cell types, but until now MMP-2 has not been reported to be involved. Therefore, distinct downstream signalling pathways are active in a tumour cell typedependent manner.…”
Section: Discussionmentioning
confidence: 97%
“…There is also evidence that PKCd can enhance cell motility, possibly by affecting the expression and activity of b1 integrins and focal adhesion kinase (Chen et al 2007, Brenner et al 2008. Furthermore, PKCd has been shown to act to promote invasiveness in prostate and breast cancer cells (Kiley et al 1999, Kharait et al 2006, Villar et al 2007, and rottlerin has been shown to completely prevent invasion induced by the integrin-activating peptide PHSRN in DU-125 prostate cancer cells (Zeng et al 2006). We have shown that both FSH and LH induce migration in ovarian cancer cells that is dependent upon ERK1/2 and PKCd signalling.…”
Section: Discussionmentioning
confidence: 99%